Effects of the glacial meltwater supply on carbonate chemistry in Bowdoin Fjord, Northwestern Greenland - Horikawa, Takahito; Nomura, Daiki; Kanna, Naoya; Fukamachi, Yasushi; Sugiyama, Shin (Frontiers in Marine Science, 2022)
To understand the effects of the glacial meltwater supply on carbonate chemistry and the air–sea CO2 flux within the fjord, water samples were collected in Bowdoin Fjord in northwestern Greenland for dissolved inorganic carbon (DIC) concentration, total alkalinity (TA), oxygen isotopic ratio (δ18O), and chlorophyll a concentration analyses in the summers of 2016 and 2017. The partial pressure of CO2 (pCO2) in surface water, calculated from DIC and TA, was less than 200 µatm, and was significantly lower than that in the atmosphere (399 ± 3 µatm). Therefore, surface water of the fjord acts as sink for CO2 in the atmosphere (–4.9 ± 0.7 mmol m–2 d–1). To evaluate the effect of freshwater and land-derived substances by glacial meltwater on pCO2 in the fjord, we calculated the changes of pCO2 in salinity and carbonate chemistry that would result from the inflow of glacial meltwater into the fjord. The calculated pCO2 was high near the calving front, where the contribution of glacier meltwater was significant. Examination of the relationship between salinity-normalized DIC and TA, which was considered DIC and TA input from the land, suggested that the land-derived high pCO2 freshwater affected mainly by the remineralization of the organic matter by bacterial activity was supplied to the Bowdoin Fjord.